Pengaruh Latihan Fartlek Terhadap Peningkatan Vo2Max pada Mahasiswa Prodi Ners Tingkat I STIKES Santa Elisabeth Medan Tahun 2024 - Sigalingging, Vina Yolanda Sari; Pakpahan, Rotua Elvina; Angelina Gultom, Kristin (STIKes Panti Rapih, 2025)
Background: Fartlek training is a type of running exercise that focuses on speed to increase heart and lung endurance, including VO2max (maximum oxygen volume). VO2max is the maximum amount of oxygen that a person can consume during intense physical activity until fatigue occurs. Lack of physical activity greatly affects a person's physical fitness which is related to VO2max levels in the body. Also known as aerobic strength which is cardiorespiratory endurance capacity Objective: This study aims to determine the effect of fartlek training on increasing VO2max in female students of the Nursing Study Program, Level 1, Santa Elisabeth Health Sciences College, Medan in 2024. Method: the method used is one-group pretest design, with a purposive sampling technique, the number of respondents is 20 people. The research instrument is a 12-minute cooper test Results: the results obtained are the average VO2max value of 1st-grade Nursing Study Program students before the fartlek exercise intervention = 13.86 ml / kgBW / min (SD5.00), the average VO2max value after the fartlek exercise intervention is 30.73 ml / kgBW / min (SD = 4.86). The statistical test used is a paired sample t-test with a p value of 0.001, meaning that there is an effect of fartlek exercise on increasing VO2mx in 1st-grade Nursing Study Program students at the Santa Elisabeth Health Sciences College in Medan. Conclusion: The effect of fartlek exercise can increase the ability or performance of the lungs and heart in taking and managing oxygen so that the body is able to carry out physical activities or sports that involve large muscles for a long time without experiencing fatigue. Fartlek exercise as an alternative to increase VO2max values ​​in 1st-grade Nursing Study Program students so that VO2max levels are getting better.